The integration of multiple HIV/AIDS projects into a coordinated national programme in China - Zunyou Wu; Yu Wang; Yurong Mao; Sheena G Sullivan; Naomi Juniper; Marc Bulterys (The World Health Organization, 2011)
External financial support from developed countries is a major resource for any developing country's national AIDS programme. The influence of donors on the content and implementation of these programmes is thus inevitable. China is a large developing country that has received considerable international support for its HIV/AIDS programme. In the early stage of the response, each large HIV/AIDS project independently implemented their activities according to their project framework. When internationally funded projects were few and the quantity of domestic support was minimal, their independent implementation did not pose a problem. When many HIV/AIDS projects were simultaneously implemented in the same locations, problems emerged such as inconsistency and overlap in data collection. China has thus coordinated and integrated all large international and domestic HIV/AIDS projects into one national programme. The process of integration began slowly and initially consisted of unified data collection. Integration is now complete and encompasses the processes of project planning, budgeting, implementation, monitoring and evaluation. The process was facilitated by having a single coordinating body, cooperation from international agencies and financial commitment from the government. Some problems were encountered during this process, such as initial reluctance from health-care staff to allocate additional time to coordinate projects. This paper describes that process of integrating domestic and foreign HIV/AIDS projects and may serve as a useful example for other developing countries for management of scarce resources.